Effect of Trichoderma Seed Dressing On Rhizoplane Mycoflora of Brassica Juncea - Walay Tagade (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Two varieties of Brassica juncea (L.) czern. and coss. cv. Varuna (containing high amount of glucosinolate) and selection EH-3 (containing very low amount of glucosinolate) were selected for rhizoplane study. The seeds of Brassica juncea cv. EH-3 and Varuna were treated with Trichoderma-talk powder. The rhizoplane mycoflora were isolated at different stages of plant growth. These mycoflora were isolated by serial root washing technique. Aspergillus sp. Curvularia lunata, Alternaria sp., F. oxysporum and Trichoderma viride are the most common fungi isolated during the investigation. Percent incidence of pathogenic fungi like Alternaria sp. were found less.